Women NGO coalitions in Egypt post January 25, 2011: prerequisites for enhanced effectiveness - Korayem, Rana Gamal (AUC Knowledge Fountain, 2013)
In the aftermath of the revolution of the 25th of January, 2011, the Egyptian women's movement has witnessed changes. The changes offered opportunities and challenges, yet with two (2) years after the revolution, the challenges continue to outweigh the opportunities. In spite of having had a newly formed parliament, the naming of a newly elected president from the conservative wing, and the coding of a new constitution, all of which held the slogan of “freedom, dignity, and social justice, 48% of the population; Egyptian women, lack clearly recognized rights in the current legal framework, their previously gained rights prior to 2011 may be compromised, and there is enough evidence that signals a perceived risk of a possible backlash on the women's agenda. Among the indicators that support this interpretation, is the fact that the national women's machinery, which is mandated to advocate for increased women's rights, is being challenged by state and none state actors. In response, women NGO coalitions and networks were formed to confront threats to women's human rights. There is a dearth of information about women NGO coalitions and networks in Egypt. Only one study in the literature studied three (3) Egyptian NGO Coalitions, taking in to account the data had been collected prior to the revolution. This research is intended to fill this gap in the literature and contribute to the documentation of the history of the Egyptian womenÃ¢â‚¬â„¢s movement. A literature review was conducted, followed by thirty (30) semi-structured interviews with gender experts and Egyptian women's activists. The researcher was also a participant observer at the 57th United Nations Commission on the Status of Women (CSW), based on which a case study was developed to study how the different actors attempted to influence the international policy agenda with regard to violence against women. The social and cultural, political, economic, and legal contexts for Egyptian women were studied to serve as the foundation of the data analysis upon completion of the data collection. A mapping of the previous and new actors in the external environment of the women's movement was conducted to support the data analysis. The findings of the study suggest that the new networks and initiatives have a higher potential to become strong coalitions, if compared to large Egyptian NGO coalitions. Advocacy techniques need to take a new shape to better influence public policies for women. The actors need to engage in networking and not networks, new partnerships should be built, and the coalition's constituencies should be widened for enhanced effectiveness. Last, but not least, there is a high need of more evidence based and scientific research, which coalitions should use in framing their messages. The study is concluded by a set of policy recommendations to guide the way forward for Egyptian women.